Hyaluronan breakdown by snake venom hyaluronidases: From toxins delivery to immunopathology - Silva de França, Felipe; Tambourgi, Denise V. (Frontiers in Immunology, 2023)
Snake venom enzymes have a broad range of molecular targets in plasma, tissues, and cells, among which hyaluronan (HA) is outstanding. HA is encountered in the extracellular matrix of diverse tissues and in the bloodstream, and its different chemical configurations dictate the diverse morphophysiological processes in which it participates. Hyaluronidases are highlighted among the enzymes involved in HA metabolism. This enzyme has been detected along the phylogenetic tree, suggesting that hyaluronidases exert multiple biological effects on different organisms. Hyaluronidases have been described in tissues, blood, and snake venoms. Snake venom hyaluronidases contribute to tissue destruction in envenomations and are called spreading factors since their action potentiates venom toxin delivery. Interestingly, snake venom hyaluronidases are clustered in Enzyme Class 3.2.1.35 together with mammalian hyaluronidases. Both mammalian and snake venom hyaluronidases of Class 3.2.1.35 act upon HA, generating low molecular weight HA fragments (LMW-HA). Curiously, LMW-HA generated by mammalian hyaluronidases becomes a damage-associated molecular pattern that is recognized by Toll-like receptors 2 and 4, triggering cell signaling cascades culminating in innate and adaptive immune responses that are characterized by lipid mediator generation, interleukin production, chemokine upregulation, dendritic cell activation and T cell proliferation. In this review, aspects of the structures and functions of HA and the hyaluronidases in both snake venoms and mammals are presented, and their activities are compared. In addition, the potential immunopathological consequences of HA degradation products generated after snakebite envenoming and their use as an adjuvant to enhance venom toxin immunogenicity for antivenom production as well as envenomation prognostic biomarker are also discussed.